The Nexus of Cultural Heritage, Identity, and Environmental Sustainability: A Bibliometric Analysis - Dennis L. Estacio; Ana Neliza B. Del Mundo-Angeles; Anjelo S. Flores; Vim Kiester C. Rivera4; Walton Wider (Future Science / FSH-PH Publications, 2026)
This research paper presents a bibliometric analysis that explores the interconnections between cultural heritage, identity, and environmental sustainability—key components of sustainable development. As global challenges arise from urbanization and climate change, the preservation of cultural heritage emerges as essential not only for maintaining community identity but also for fostering environmental and economic resilience. Through a thorough examination of scholarly literature over the past two decades, this study identifies primary research themes, emerging trends, and leading contributors in interdisciplinary scholarship concerning heritage conservation and sustainability. Employing various databases, including Scopus, Web of Science, and Google Scholar, the analysis utilizes tools such as VOSviewer and Bibliometrix for data visualization and citation analysis. The results reveal distinct co-citation clusters focused on topics like cultural tourism, urban sustainability, the governance of cultural heritage, and the strategic management of landscapes. The findings underline the critical role of community engagement, innovative policy-making, and education in enhancing heritage conservation efforts. The study advocates for a reconceptualization of sustainability to encompass cultural dimensions, emphasizing the need for integrative approaches that harmonize heritage preservation with environmental and economic development. This research ultimately aims to inform stakeholders—from policymakers to practitioners—about the essential nexus between cultural heritage and sustainable development, offering practical recommendations for fostering a resilient future.